(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In article al-Farabi attempt to carry out a task which continues to excite scientists – to try on philosophy/mind with belief/religion. Such important questions for al-Farabi as “reconciliation”, contradiction of elimination between Platon and Aristotle’s philosophies, and as contradiction of elimination between Islamic outlook and views of Ancient Greek philosophy are analyzed. Al-Farabi considers communication between religion and philosophy in three aspects: 1) Attitude towards the Founder. As the main difficulty that in Islam the concept of God is the key; for Aristotle the concept of the Prime causes isn’t central; 2) The concept “Vakhy” – “divine revelation”, absent in the Greek philosophy. Therefore alFarabi was compelled to make any comments concerning a prophecy, revelation and miracles shown by prophets; 3) The relation between commoners incapable of philosophy (“а’ввам”) and the philosophers being the elite (“хаввас”). Externally this question understood al-Farabi from the pedagogical point of view; actually it was deeply connected with a problem of reconciliation of philosophy and religion. Proceeding from it the special attention is paid to the analysis of interrelation of religion and philosophy of al-Farabi, the role of values of Islam in formation of universal values. Key words: emanation, Islam philosophy, interrelation of religion and philosophy.